Architecture: A Missing Piece in Real-estate Studies of Sustainable Houses. (2015) - Fadaei, Shahrzad; Iulo, Lisa D.; Yoshida, Jiro
Abstract: In the era of ecological and economic crisis, while the trend has drastically changed, most single-family houses in the United States are still built in a conventional way. The problem has roots in the fact that ecologically sustainable buildings are often initially more costly compared to ordinary ones. In a number of studies, lower life-cycle cost and longer economic life of sustainable buildings have been considered as a beneficial effect on the cost, having a positive impact in the real estate market of green residential properties. On the other hand, there has been research discussing the impact of architecture and architectural decisions on real estate and marketing of the buildings. Yet a lack of research investigating the importance of architecture in the marketplace of green buildings especially homes is evident. This study presents current literature and an analysis of the building appraisal process in different locations and mainly in the United States with special attention to the residential sector. The theoretical conclusion finds that architectural decisions can have a positive impact on the price of sustainable homes. This paper finally suggests direction for future research to be conducted in the interest of empirically proving this finding.